Development of Home-Based Physiotherapy Device For Monitoring of Muscle Treatment - Abdullah, Nazmi; Wan Mahmud, Wan Mahani Hafizah (Evolution in Electrical and Electronic Engineering, 2021)
Most studies of muscle treatment are hospital-based. However, to build a better environment in medical purpose, the convenient technologies are very useful. Due to the pandemic Covid-19 , the arrangement of face-to-face consultation with physiotherapist will increase the health risk. In order to reduce these complications, a telemedicine concept and compact assistive device is designed. The muscle treatment monitoring device is developed as monitoring tools for the patient daily use. The aim of this project is to determine whether muscle treatment monitoring device performed on patient would be effective at improving the muscle condition. For this purpose, the contraction and movement result was recorded in a voltage format. The larger muscle movement will provide a larger voltage and vice versa. The data set include 5 students from UTHM. The results show a high correlation between movement and voltage. To conclude, the development of this home based muscle monitoring device has proven to be reliable and could be used as an alternative physiotherapy process at home.